Management Of Path Of Insertion In Fixed Prosthodontic For Mesially Tilted Mandibular Second Molars : A Literature Review - Izzulhaq Fauzandhi Arsa; Pamungkas Handy Mulyawan (International Journal of Health Engineering and Technology, 2026)
The loss of posterior teeth that is not promptly rehabilitated may result in tooth movement toward the edentulous space, leading to tilting of the abutment teeth. One of the most common conditions is mesial tilting of the mandibular second molar following the loss of the mandibular first molar, which may disrupt occlusal relationships, affect abutment alignment, and create difficulties in achieving an ideal path of insertion during fixed prosthodontic treatment. An inappropriate path of insertion may increase the complexity of tooth preparation and compromise the long-term success of the restoration. This study aimed to review the management of path of insertion in fixed prosthodontic treatment involving mesially tilted mandibular second molars through a literature review approach. The literature search was conducted using Google Scholar, PubMed, and ScienceDirect for articles published between 2016 and 2026. The findings indicated that successful management of path of insertion depends on proper abutment evaluation based on biomechanical principles and Ante's Law, as well as the selection of an appropriate treatment strategy according to the clinical condition. Several treatment options, including modified tooth preparation using a proximal half crown, orthodontic uprighting, non-rigid connector, and telescopic crown, have been reported to improve the path of insertion in selected cases. In conclusion, selecting an appropriate treatment strategy based on clinical conditions and biomechanical principles may help achieve an optimal path of insertion, thereby supporting the long-term success of fixed prosthodontic treatment.